A systematic review of metacognitive dynamics in secondary physics education - Osman, Norhidayah; Mahmud, Siti Nur Diyana; Arsad, Nurazidawati Mohamad (Institute of Advanced Engineering and Science, 2025)
Metacognitive strategies are effective in enhancing secondary school students’ performance in physics, a key science, technology, engineering, and mathematics (STEM) subject that poses challenges due to its conceptual complexity and the need for higher-order thinking skills. This study systematically reviews the impact of metacognitive strategies on student performance in physics from 2014 to 2024. The research objectives include identifying trends, advantages, and challenges of these strategies. Using preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, 25 studies were selected from databases like Web of Science (WoS) and Scopus, involving diverse respondents. Research instruments included surveys, interviews, and standardized tests to assess metacognitive awareness and academic performance. Analysis revealed a preference for quantitative methods (88%), with qualitative (8%) and mixed methods (4%) also contributing insights. Results indicate that metacognitive strategies enhance conceptual understanding, problem-solving skills, motivation, engagement, and academic performance while reducing gender gaps. However, challenges include implementation complexity, time constraints, student resistance, assessment difficulties, and variability in effectiveness. The findings underscore the need for comprehensive teacher training and innovative instructional designs to integrate metacognitive strategies effectively. These strategies hold promise for transforming physics education and promoting equitable student outcomes. Future research should focus on developing tailored approaches and innovative assessment methods to optimize the implementation of metacognitive strategies across diverse educational contexts.